Exploring the use of the conversation starter game QUONVO™ on the soft skills and STEM identity of undergraduate students - King, Candace; Flynt, Alex; Patrick Kirby; Hannah McDuffie; Kendrick Buford; Rachel Gisewhite; Waikinya J.S. Clanton (American Journal of STEM Education, 2026)
A major gap in the research on soft skills is how to efficiently integrate soft skills training  that actually aligns with the needs of employers. Game-based learning has become a popular method for teaching knowledge and skills. This project explores the use of a non-digital conversation starter game, QUONVO™, as an informal soft-skills training tool by measuring how gameplay with QUONVO™ can influence undergraduate STEM majors' perception of their soft skills (specifically communication and critical thinking) and their STEM identity. Overall, this study found that QUONVO™ positively impacted students’ STEM identity and soft skills development. Gameplay discussions incorporated personal experiences, course content, and professional knowledge, with students demonstrating independence in expressing their ideas.